Analisis Pengaruh Efektivitas, Efisiensi, dan Kontribusi Sektor Pariwisata terhadap Pendapatan Asli Daerah (PAD) Kota Bukittinggi Tahun 2010-2019 - Titi Andriza; Nelvirita Nelvirita (Universitas Negeri Padang, 2022)
The purpose of this study is to find out how the relationship between the effectiveness, efficiency and contribution of the tourism sector to the local revenue of the city of Bukittinggi from 2010 to 2019. The research population is all taxes and levies on the tourism sector of the city of Bukittinggi using the sample technique method. This study uses a quantitative method with a descriptive approach and correlation test. The novelty of this research is to examine the relationship of each independent variable to the dependent variable so that it explains in more detail the relationship/relationship. The results show that the effectiveness of the tourism sector in Bukittinggi City has an average effectiveness level of 88% which is classified as effective and has a negative perfect linear relationship to local revenue, the efficiency of the tourism sector in Bukittinggi City has an average efficiency level of 14% classified as efficient and has Positive perfect linear relationship to local revenue and contribution of the tourism sector Bukittinggi City has an average contribution rate of 43% which is classified as making a good contribution and has a perfect linear relationship to local revenue.